1992
DOI: 10.1002/jmv.1890380306
|View full text |Cite
|
Sign up to set email alerts
|

Detection of herpesvirus DNA in the large intestine of patients with ulcerative colitis and Crohn's disease using the nested polymerase chain reaction

Abstract: The prevalence of herpesvirus DNA was examined in inflammatory bowel disease tissue. DNA was extracted from resection and biopsy specimens of the large intestine from patients with ulcerative colitis (n = 21), patients with Crohn's disease (n = 29), and patients with noninflammatory bowel disease (controls) (n = 21). The nested polymerase chain reaction was used to detect viral DNA using primer pairs specific for either cytomegalovirus (CMV), herpes simplex virus 1 (HSV1), human herpesvirus 6 (HHV6), varicella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
3
3

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(114 citation statements)
references
References 23 publications
6
102
3
3
Order By: Relevance
“…A study that used PCR showed positive detection in about 66% of CD patients, 81% in UC patients, and 29% in controls [9] .…”
Section: Patient Selection Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A study that used PCR showed positive detection in about 66% of CD patients, 81% in UC patients, and 29% in controls [9] .…”
Section: Patient Selection Methodsmentioning
confidence: 99%
“…The first report about the possible role of cytomegalovirus in IBD dates to 1961 when Powell [31] described a case of ulcerative colitis and cytomegalic inclusion disease. After many sporadic reports over the last decade, the topic has regained attention due to more frequent publications of case-reports or small series studies in which the virus provided a worsening prognosis influence, sometimes promoting disease initiation or otherwise acting as a bystander [9] . The coincidental detection of primary CMV infection at the first appearance of IBD is reported in some casereports [32,33] , underlining the ability of CMV proteins to enhance pro-inflammatory cytokines that are able to maintain a local colonic inflammation with an immune response.…”
Section: And Acquired Immunodeficiency Syndromes or Immunosuppresmentioning
confidence: 99%
See 2 more Smart Citations
“…Stringent control measures were applied to prevent both carryover and contamination (65). In brief, DNA was extracted from the circle of DBS by adding 35 μl of cell culture medium (minimum essential medium) followed by thermal shock (55˚C for 60 min and 100˚C for 7 min, centrifugation at 11,200 rcf, and the supernatant was frozen at −80˚C overnight) and amplified using a nested polymerase chain reaction (PCR) designed to amplify one region in the GP58 gene (66). The first round of CMV-DNA amplification was carried out starting with 5 μl extract in 45 μl PCR mixture (10 mM TrisHCl, 1.5 mM MgCl2,50 mM KCl, 0.1% triton X-100, 200 mM dNTP) containing 1U Taq-polymerase (DyNAzyme™ II DNA Polymerase; Finnzymes, Thermo Fisher Scientific Inc. Ratastie, Vantaa, Finland) and the primers (1 mM) necessary for amplification.…”
Section: Methodsmentioning
confidence: 99%